PENGARUH LATIHAN KNEE TUCK JUMP TERHADAP POWER OTOT TUNGKAI PADA DOJO LEMBAGA KARATE DO INDONESIA PEKANBARU - Gilang Gumelar; Ramadi Ramadi; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: From observations made by researchers in the Karate DojoIndonesia Pekanbaru during training, researchers looked at and found deficiencies in leg muscles in kicking, so that when kicking was less than optimal. This kick is less well done which causes the kick to be easily on the edge of the opponent. The purpose of this study was to determine the effect of knee tuck jump training on leg muscle power in the dojo of the Karate Do Pekanbaru Indonesian. This research was conducted in July untilAugust boast. The data in this study are all populations totaling 6 people all of which are sampled. The vertical jump test instrument which was carried out by descriptive analysis and liliefors test resulted in pree test vestical jump with an average of 39.33. After that the sample was given a knee tuck jump training program for 16 meetings at the male dojo athlete of the Pekanbaru karate do Indonesia institute, amounting to 6people and an average vertical jump test post of 46. The data obtained were analyzed descriptively, then further testing Research hypotheses that have been submitted according to the problem are: "There is an effect of knee tuck jump (X) exercise on increasing leg muscle power (Y). Based on the analysis conducted, the value of t-test between the initial test and the final test of knee tuck jump training on leg muscle power with a table at a significant level of 0.05 with degrees of freedom N - 1 (6-1 = 5). Thisshows that the value of tcount (13.59)> ttable (2.015) thus it can be concluded that the hypothesis which states that there is an effect of knee tuck jump (X) exercise on leg muscle power (Y) in the dojo of the Karate Do Indonesia Pekanbaru.Key Words: Knee Tuck Jump Exercise, Leg Muscle Power